OFR-123(6)-78 Advancement Of Mine Ventilation Network Analysis From Art To Science - Volume VI Application Of PSU/MVS To The Analysis Of Modifications To Existing Ventilation Systems - G. W. Luxbacher (The National Institute for Occupational Safety and Health (NIOSH), 1977)
This volume describes the use of the Penn State Mine Ventilation Simulator (PSU/MVS) to model existing mine ventilation systems and, in addition, to evaluate the effect of system modifications. Ventilation survey methods designed to insure computer input data of sufficient accuracy for simulation purposes are covered in comprehensive detail, including quantity and pressure measurement and fan performance testing. The development of input data from ventilation survey results is discussed and illustrated by the use of an actual field survey. Two programs, written in FORTRAN IV with WATFIV, are presented to calculate airway head losses from altimeter pressure measurements. An existing coal mine ventilation system is analyzed and modifications to the system are simulated and evaluated. In addition the application of the PSU/MVS to non-coal mines is briefly discussed. An extensive bibliography on ventilation surveying and simulation is included.